Disadvantaged populations in maternal health in China who and why? - Beibei Yuan; Xu Qian; Sarah Thomsen (Taylor & Francis Group, 2013)
Background: China has made impressive progress towards the Millennium Development Goal (MDG) for maternal and reproductive health, but ensuring that progress reaches all segments of the population remains a challenge for policy makers. The aim of this review is to map disadvantaged populations in terms of maternal health in China, and to explain the causes of these inequities to promote policy action. Methods: We searched PUBMED, Popline, Proquest and WanFang and included primary studies conducted in mainland China. Experts were also contacted to identify additional studies. Disadvantaged populations in terms of MDG 5 and the reasons for this disadvantage explored by authors were identified and coded based on the conceptual framework developed by the WHO Commission on the Social Determinants of Health. Results: In China, differences in maternal health service utilization and the maternal mortality ratio among different income groups, and among regions with different socio-economic development still exist, although these differences are narrowing. Groups with low levels of education and ethnic minorities utilize maternal health care less frequently and experience higher maternal mortality, although we could not determine whether these differences have changed in the last decade. Rural-to-urban migrants use maternal health care and contraception to a lower extent than permanent residents of cities, and differential maternal mortality shows a widening trend among these groups. Gender inequity also contributes to the disadvantaged position of women. Intermediary factors that explain these inequities include material circumstances such as long distances to health facilities for women living in remote areas, behavioral factors such as traditional beliefs that result in reduced care seeking among ethnic minorities, and health system determinants such as out-of-pocket payments posing financial barriers for the poor. Conclusions: Inequity in maternal health continues to be an issue worthy of greater programmatic and monitoring efforts in China.